KEMAKSUMAN NABI: KAJIAN TERHADAP AYAT-AYAT âITÃB TERHADAP NABI MUHAMMAD SAW - Sriwahyuni, Sriwahyuni (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2017)
This article aims to understand what the concept of the infallibility of prophets and messengers by seeing some interpretations of some verses contained in the Qoran are considered as âitÃ¢b (admonition/warning) for one of the prophets, he is the prophet Muhammad pbu. The data of this study was obtained through primary  literature, it is an interpretation literature (kitab tafsir) of classic interpreter (mufassir) and some modern interpreters. This study was discussed in the descriptive-comparative analysis by using the infallibility (âismah )theory . Initially, the writer described admonitionâs verses  that will be studied by comparing it with two other interpretations, and then analyzed it. Thus it was found that interpreters  differed in recognizing the exictence of admonitionâs verses to the prophet Muhammad pbu  in the Qoran. Finally, the study has analyzed and was found that the admonitions were not for a mistake or a sin that will eliminate  the infallibility attribute that had attached to him, but it was as manifestations of the compassion of Allah to the Prophet in  order to not too forces his self in preaching, because however he had do all the commands of Allah to convey  all of his message or revelation.